MY HEALTH AND DISEASE PHILOSOPHY - Yablucnasky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The problems of health and disease are discussed. Measure of health and disease are determined. Measure include the norms. Health measure has its own norms. Disease measure has its own norms. The principle of disease optimality is entered as the disease norm. I prove that wrong to oppose health and disease. Health and the disease can only be compared. The disease cure or the disease itself requires considerable health resources. The significance of the philosophy of disease and health for the medicine is discussed.